The impact of climate change in cocoa production in Colombia, Ecuador and Peru - Castro, Fabio; Bunn, Christian (2022)
These data contain spatial information on agroclimatic zones for cocoa farming in Colombia, Ecuador and Peru, as well as impact gradient layers that illustrate the effect that climate change might have on cocoa crops in the same three countries.